Attitudes and behaviors of university PE students towards the use of computers - Bebetsos, E.; Kouli, O.; Antoniou, P. (International Journal of Computer Science in Sport, 2007)
The aim of this study was to discover the attitudes and behaviors of Greek Physical Education students towards the subject of computers, and the changes that might have occurred in these attitudes and behaviors, as influenced by general information provided in their classrooms. The sample consisted of 244 freshmen students, 119 males and 125 females. They completed a planned behavior questionnaire in the beginning and again in the end of a semester period. The results indicated gender differences and contribution of the variables "knowledge" and "information". Overall, the results supported the use of the instrument as an appropriate tool in order to investigate attitudes and behaviors towards the use of computers.